1982
DOI: 10.1139/b82-080
|View full text |Cite
|
Sign up to set email alerts
|

The genus Chenopodium in Canada

Abstract: A key, descriptions of morphological characters (especially those of the seed testa and pericarp), chromosome numbers, and the distributions of 31 species of Chenopodium occurring in Canada are presented. Many names of the native taxa are typified and several nomenclatural problems are clarified. Chenopodium album L. var. missouriense (Aellen) I. J. Bassett et C. W. Crompton comb. nov. is reported here for the first time as occurring in Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…The lamina size of the lower leaves, petiole length of upper or lower leaves and stem height are the most variable traits in almost all populations. The characteristics of the seed dimensions (i.e., length, width and ratio between them) are some of the most con- The high variability of stem height and leaf characters of the species from Chenopodium senso lato, and the lack of any considerable variability in seed characters have been acknowledged by researchers of the genus from various parts of the world (KOWAL 1953, ENGSTRAND and GUSTAFSSON 1972-1974, REYNOLDS and CRAUFORD 1980, BASSET and CROMPTON 1982, DOSTÁLEK et al 1990, AL-TURKI and GHAFOOR 1996, UOTILA 2001. The main source of phenotype variation in all species is the interpopulation variation.…”
Section: Discussionmentioning
confidence: 99%
“…The lamina size of the lower leaves, petiole length of upper or lower leaves and stem height are the most variable traits in almost all populations. The characteristics of the seed dimensions (i.e., length, width and ratio between them) are some of the most con- The high variability of stem height and leaf characters of the species from Chenopodium senso lato, and the lack of any considerable variability in seed characters have been acknowledged by researchers of the genus from various parts of the world (KOWAL 1953, ENGSTRAND and GUSTAFSSON 1972-1974, REYNOLDS and CRAUFORD 1980, BASSET and CROMPTON 1982, DOSTÁLEK et al 1990, AL-TURKI and GHAFOOR 1996, UOTILA 2001. The main source of phenotype variation in all species is the interpopulation variation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the macrofossil content of the sample is similar to those immediately above and below the tephra at Station 4. Porsild and Cody (1980); Chenopodium gigantospermum (d) is from Bassett and Crompton (1982). Distribution of the carabid beetles Dyschirius laevifasciatus (e) and Bradycellus lecontei (f) from Lindroth (1968), Bousquet (1988) and D. Kavanaugh (California Acad, of Sciences, pers.…”
Section: Stations Other Than Stationmentioning
confidence: 99%
“…The insects such as Coleophora suaedivora (Coleophoridae) and Phthozimaea suaedella (Gelechidae) feed on leaves and seeds. Bassett & Crompton (2011) recorded that S. maritima flowers during July-September and is wind-pollinated. Naskar & Mandal (1999) reported that S. maritima is pollinated by wind, water currents and flies.…”
Section: Introductionmentioning
confidence: 99%
“…The flowers are nectar-less and hence insect activity is absent. Bassett & Crompton (2011) recorded that S. maritima is windpollinated. Naskar & Mandal (1999) reported that S. maritima is pollinated by wind, water currents and flies.…”
mentioning
confidence: 99%